Motivación, una experiencia por descubrir en matemáticas - Molina Murcia, Yeison Ferney (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Eng: The aim of this research project is to analyze the motivation of eleventh grade students of Institución Educativa Técnica Pío Alberto Ferro Peña from Chiquinquirá, Boyacá, applied in the math class which the topic was the concepts of triangles solution. Besides, learning and motivation regarding to the math class were involved as well as the way to apply them in the daily life. Also, the theory of didactic situations in the design and application of the sequences were treated to help on the development of the research. The project was a mixed type research, since both qualitative and quantitative aspects were taken into account in this development of collecting and analyzing data. Besides, didactic sequences were designed and applied, which allowed to see the academic progress in terms to the math’s goal and the level of motivation shown by the students during their development. The findings of the project were analyzed by the researchers taking into account the fundamental aspects of Didactic Situations Theory. Finally, it can be concluded that the motivation of this group of students towards the mathematics class was improved. Thanks to the implementation of aspects such as the contextualization of the situations raised, the use of technological tools, the involvement of the historical and anecdotal part of the mathematical object; likewise, a better and close interaction between the teacher and the student that allowed the use of the word with greater naturalness and more spontaneous participation.